Implications of Differences in Professional Certification Authority between Bank Indonesia and the Financial Services Authority on the Effectiveness and Mitigation of Systemic Risk in the Financial Services Industry - Miftakul Azis; Zudan Arief Fakrulloh (PT. ALHAFI BERKAH INDONESIA, 2025)
This study examines the problem of disharmony in the regulation and implementation of professional certification in the financial services sector after the issuance of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK Law). The main focus of the study is the analysis of the overlapping authority between the Financial Services Authority (OJK) and Bank Indonesia (BI) and the impact of granting certification authority to professional associations as stated in Article 261 of the PPSK Law. The provision is considered to create dualism in the certification system that weakens the integrity and accountability of the competence of professional personnel in the financial industry. This study reviews the differences in approach between the Professional Certification Institution (LSP) based on the Indonesian National Work Competency Standards (SKKNI) and certification organized by professional associations and evaluates its implementation by OJK and BI. Through a juridical-normative approach and supported by empirical data from strategic institutions, this study finds that the lack of system integration and lack of institutional coordination have an impact on the non-uniformity of competency standards and the potential for systemic risk in the financial services sector. Therefore, a policy harmonization model is needed that emphasizes the importance of integrating the SKKNI-based certification system, with LSP as the main implementer and professional associations as supporting partners, to ensure equal and credible HR quality across all financial services subsectors.